Hit-and-Run or Hit-and-Stay? Unintended Effects of a Stricter BAC Limit - Michael French; Gulcin Gumus (Institute of Labor Economics (IZA), 2024)
Although they comprise a relatively small subset of all traffic deaths, hit-and-run fatalities are both contemptible and preventable. We analyze longitudinal data from 1982-2008 to examine the effects of blood alcohol concentration (BAC) laws on hit-and-run traffic fatalities. Our results suggest that lower BAC limits may have an unintended consequence of increasing hit-and-run fatalities, while a similar effect is absent for non-hit-and-run fatalities. Specifically, we find that adoption of a .08 BAC limit is associated with an 8.3% increase in hit-and-run fatalities. This unintended effect is more pronounced in urban areas and during weekends, which are typical settings for hit-and-run incidents.
Keywords: H73; I12; I18; 330; traffic fatalities; hit-and-run; BAC; DUI; FARS